SUBJECTIVE AND OBJECTIVE ESTIMATION OF THE LEVEL OF PHYSICAL EDUCATION IN SERVICE OF CONSERVING HEALTH STATUS IMPROVEMENT - Dragan Krivokapić; Branislav Radulović; Olivera Krivokapić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2014)
Introduction: Results of ever increasing number of research indicating to number of benefits of regular physical activity has influenced formation of many directions on recommended volume and intensity of exercise which is in the service of keeping and improving of a modern man`s health. From the aspect of risk estimation on health endangering, the major attention should be paid on identification of people who do not fulfill even necessary minimums regarding doing the physical activity. Participation in some kind of physical activity represents the most variable component of the overall daily calorie consumption of sedentary population because it mostly depends on the level of knowledge on influence of the physical activity, degree of self control and persistence of each individual to persist in attempting to keep and improve their health. Methods: This paper was conceived on methods of the American College for Sports Medicine ACSM (2009) which is one of the most referent sources in promotion of positive effects of physical activity on a modern man`s health. According to directions in the above mentioned source, there will be five elements of physical form to be analyzed that are related to health: cardio respiratory form, defined as a competence of cardiovascular and respiratory system to `deliver` oxygen to active musculature during continued physical activity; body structure referring to relative or percent share of different tissues within the body and which are related to health status; muscular strength, representing the ability of the human body to do the activity for which a high level of muscular strength is necessary; muscular endurance, defined as an ability of muscles or muscular group to do repeated contractions within a long time period; flexibility, representing the ability to make big amplitude moves in a particular joint. Results: Results of so far research have established a clear connection between physical activity and health. One of the most important publications in which this connection is emphasized is the report of the American Ministry of Health, called Physical activity and health (1996), which gives a number of useful effects on health status of people who participated in some form of physical activity. Exact minimal volume and intensity of physical activity enough to cause positive effects on health status is still unknown, so the estimation of elements of physical form related to health became important for many institutions occupied with health of people. Discussion: For each of the above mentioned elements of physical form related to health, there were different subjective and objective procedures established that can be used for their estimation. Carpensen CJ. Powell KE, Cristenson GM Besides (1985), it is very important to take into account a clear aim for which a certain estimation is done, because it enables implementation of the most appropriate protocol for estimation of each element of physical form. In that sense, subjective and objective estimation of the level of physical activity of an individual is essential for preservation and improvement of their health status. References: American College for Sports Medicine, Guildelines for exericise testing and Prescription.8th ed. Philadelphia: 2009 Lippincott Williams&Wilkins, 248-52. Carpensen CJ, Powell KE, Cristenson GM (1985). Physical activity , ehercise, and physical fitness: definitions and distinctions for healt-related research. Public Health Rep., 100(2), 126-31. U.S. Department of Healt and Human Services and Centers for DiseaseControl and Prevention. Physical Activity and health: A report of the Surgeon General. Atlanta (GA): 1996 National Center for Chronic Disease Prevention and Health Promotion, 89-90.